2020
DOI: 10.1007/s10980-020-00988-9
|View full text |Cite
|
Sign up to set email alerts
|

Variation in parasitoid attraction to herbivore-infested plants and alternative host plant cover mediate tritrophic interactions at the landscape scale

Abstract: Context Tritrophic interactions may be affected by local factors and the broader landscape context. At small spatial scales, carnivorous enemies of herbivorous insects use herbivore-induced plant volatiles (HIPVs) to find herbivores, but it is unknown whether variation in plant attractiveness due to differential HIPV emission can enhance recruitment of carnivores from the wider landscape. Objectives We studied whether parasitism of caterpillars of the butterfly Pieris brassicae on white cabbage was influenced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Maize plants of 10 to 21 days old (3-9 leaf stages) emit induced volatiles when Spodoptera exigua or S. littoralis feed on the young leaves and consequently attract more natural enemies compared to undamaged plants (D'Alessandro et al 2009;Turlings et al 1991;Fritzsche-Hoballah and Turlings 2001). While most studies on HIPVs and natural enemies have been conducted under controlled laboratory conditions, some have demonstrated their effects under field environments (Aartsma et al 2019(Aartsma et al , 2020Bernasconi Ockroy et al 2001;De Lange et al 2018;Drukker et al 1995;Poelman et al 2009;Shimoda et al 1997). Furthermore, a recent study using 3-leaves stage (9-12 days old) maize plants confirmed that S. frugiperda has lower HIPVs induction on maize than other Spodoptera species (De Lange et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Maize plants of 10 to 21 days old (3-9 leaf stages) emit induced volatiles when Spodoptera exigua or S. littoralis feed on the young leaves and consequently attract more natural enemies compared to undamaged plants (D'Alessandro et al 2009;Turlings et al 1991;Fritzsche-Hoballah and Turlings 2001). While most studies on HIPVs and natural enemies have been conducted under controlled laboratory conditions, some have demonstrated their effects under field environments (Aartsma et al 2019(Aartsma et al , 2020Bernasconi Ockroy et al 2001;De Lange et al 2018;Drukker et al 1995;Poelman et al 2009;Shimoda et al 1997). Furthermore, a recent study using 3-leaves stage (9-12 days old) maize plants confirmed that S. frugiperda has lower HIPVs induction on maize than other Spodoptera species (De Lange et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…We do not want to rule out other factors that could mask some important environmental variables, Further analysis over time and space is thus needed to understand better how the effect of the landscape depends on other abiotic factors such as temperature, rainfall, photoperiod or other variables related to the development of the olive tree, in addition to the role of complementary local scale variables that strictly depend on the traits of pest and of the natural enemies community. In fact, some land use variables may not completely capture the specific ecological prerequisites of such organisms (Aartsma et al, 2020).We also found a small-scale crossover effects on the infestation rate but not an overall effect of single variables. The role of the landscape on the olive leaf gall midge needs more investigation.…”
Section: Discussionmentioning
confidence: 59%
“…Although we were not able to find any studies that have directly measured the effect of land use change on plant indirect defenses in natural plant populations, the little evidence we have suggests that there could be differential selection by natural enemies on indirect defense traits. In a study done on cabbage infested with herbivore Pieris brassicae placed in different landscapes, it was found that the induction of plant volatiles in response to herbivory can mediate the effect on parasitism ( Aartsma et al, 2020 ). To test this, two different accessions of cabbage were used.…”
Section: Land Use Change Affects Indirect Defenses Mediated By Naturmentioning
confidence: 99%